Desarrollo e implementación del plan de mantenimiento para los equipos de la empresa Prodehogar Ltda. (2018)
For the development of the Project, the present maintenance situation was initially diagnosed, the information was collected, resumes formats, technical sheets, and other documents containing information about the equipment, work requests, work orders and resumes. Additionally, the equipment inventory was carried out, and the company equipment manuals were searched. This information was compiled within the developed application. After having grouped all this information and having established with the department of production and accounting, an encoding that allowed to categorize the equipment with respect to the areas covered by the company. The selection of the areas in which the analysis was to be carried out was started, based on the registry of corrective works and unscheduled tasks registered during the implementation period, resulting in the areas of metalworking and painting.